Vorklinische Untersuchung zur Organverteilung und Strahlenbelastung von Radiojod-Jodlisurid - Buchali, K.; Flade, H.; Johannsen, B.; Pink, V.; Herold, U.; Harhammer, R.; Horowski, R. (Nuklearmedizin - NuclearMedicine, 1991)
The distribution in rats of 125l-iodolisuride was studied. Three rats each were sacrificed at fixed intervals between 5 min and 24 h p. i., and the radioactivity was measured in isolated organs and parts of the body. The organ distribution and biexponential blood disappearance were similar to values for unlabeled lisuride. The radiation dose was estimated for man assuming a 123l label. The resulting doses were comparable to those from other radiopharmaceuticals in clinical use.